Vztah koncentrace kovů a lyzozymu v placentách žen s intrauterinní růstovou retardací plodu - Richter, J; Hájek, Zdeněk; Pfeifer, I; Šubrt, P (Česká gynekologie, 1997)
In a group of women who gave birth to a foetus with marked growth retardation and 27 women who were delivered of eutrophic neonates the lead, cadmium, zinc and lysozyme levels in placental tissue were assessed. The investigation revealed the following results: the lead level was in the investigated group significantly higher than in the control group (15.24 ng/g vs. 11.31 ng/g). Conversely the zinc levels were significantly higher in the control group (20.52 μg/g vs. 14.3 μg/g of placental tissue). The lead, cadmium and lysozyme values rise with the womens' age in the examined placentae, while the zinc levels decline. With the elevated zinc level the lead and cadmium content in the placentae of the exposed group declines. The lysozyme values increase along with the rise of all investigated elements with the exception of zinc, where the dynamics are reversed. The findings justify the recommendation of zinc supplementation during pregnancy.
Keywords: Placental Function Tests; dospělí; Metals; testy funkce placenty; Fetal Growth Retardation; lidé; Female; Pregnancy; těhotenství; Muramidase; růstová retardace plodu; Adult; kovy; muramidasa; ženské pohlaví; Humans